Reshaping Economic Geography in East Asia - Huang, Yukon; Magnoli Bocchi, Alessandro (World Bank, 2012)
Reshaping economic geography in East Asia illustrates how extensively spatial factors have influenced and informed by growth and development in the region. This study was conceived as a companion volume to and informed by the World Development Report (WDR) 2009: reshaping economic geography. By providing case studies and illustrative examples and by deepening the understanding of the forces of economic geography in the East Asia region, this work helped to substantiate some of the key concepts in the WDR 2009. There is full consistency in terms of the analytical framework used and broad agreement on how economic geography has influenced growth trends across a diverse range of countries. Reshaping economic geography in East Asia also highlights the dramatic urbanization process under way in the region, evidenced by the number of globally recognized 'mega cities'. Seven of the world's 21 mega cities are in East Asia. Cities in East Asia generate about three-quarters of annual output and between a half and two-thirds of exports. Often, much of this is concentrated in one major city: Bangkok. Bangkok accounts for 40 percent of Thailand's gross domestic product (GDP) and Manila for 30 percent. Other major centers such as Guangzhou, Jakarta, Seoul, Shanghai, and Tokyo are seen as driving their economies. East Asian cities have been able to deliver the agglomeration benefits required for growth and are now exceptionally well connected to the global economy. The region, excluding Japan, is home to 16 of the largest 25 seaports in the world and 14 of the largest 25 container ports. Without this improved connectivity, the region's rapid expansion in trade volumes will not have been possible. This collection of studies is organized in four sections. The first section comprises chapters dealing with the 'context and concepts' for this volume. The second deals with Southeast Asia, specifically, the Association of South East Asian Nations (ASEAN) countries. The third deals with Northeast Asia: China and the Republic of Korea, and the fourth section provide an overview of lessons learned. The time perspective for most of the studies spans several decades; in many cases, outcomes and policies can be traced back half a century or more.